2019
DOI: 10.1182/bloodadvances.2018028761
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of single-agent ibrutinib in patients with chronic lymphocytic leukemia in 3 pivotal studies

Abstract: Ibrutinib, a first-in-class once-daily oral Bruton tyrosine kinase inhibitor indicated for chronic lymphocytic leukemia (CLL), is continued until progressive disease or unacceptable toxicity. We conducted an integrated safety analysis of single-agent ibrutinib from randomized phase 3 studies PCYC-1112 (RESONATE, n = 195) and PCYC-1115/1116 (RESONATE-2, n = 135), and examined longer-term safety separately in the phase 1b/2 PCYC-1102/1103 study (n = 94, 420 mg/d). In the integrated analysis (ibrutinib treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 27 publications
3
96
0
2
Order By: Relevance
“…In addition, BMX is a target of ibrutinib, a small molecule therapy that targets the BTK pathway. Ibrutinib is being used in several clinical trials for patients with mature B‐cell malignancies including relapsed/refractory chronic lymphocytic leukaemia (Coutre et al , ; Nuttall et al , ; Shanafelt et al , ), small lymphocytic lymphoma (Coutre et al , ), and mantle cell lymphoma (Wang et al , ) and BMX expression in 4/6 adult B‐ALL patients in this study, the antigenicity of BMX as shown by proto‐array analysis and recent study showing the ability of ibrutinib to target pre‐BCR signalling in B‐ALL (Kim et al , ) all suggest the value of using ibrutinib to treat adults with B‐ALL.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, BMX is a target of ibrutinib, a small molecule therapy that targets the BTK pathway. Ibrutinib is being used in several clinical trials for patients with mature B‐cell malignancies including relapsed/refractory chronic lymphocytic leukaemia (Coutre et al , ; Nuttall et al , ; Shanafelt et al , ), small lymphocytic lymphoma (Coutre et al , ), and mantle cell lymphoma (Wang et al , ) and BMX expression in 4/6 adult B‐ALL patients in this study, the antigenicity of BMX as shown by proto‐array analysis and recent study showing the ability of ibrutinib to target pre‐BCR signalling in B‐ALL (Kim et al , ) all suggest the value of using ibrutinib to treat adults with B‐ALL.…”
Section: Discussionsupporting
confidence: 63%
“…Of note, PFS benefit with ibrutinib remained in the final analysis after 6‐year of follow‐up . Patients with ≥2 prior therapies and those with TP53 or SF3B1 mutations had shorter PFS …”
Section: Early Trials Of Ibrutinib Single Agent In the Setting Of R/rmentioning
confidence: 96%
“…The most common AEs contributing to drug discontinuation were pneumonia (n = 4), anemia (n = 3), and atrial fibrillation (n = 3). 18 Of note, PFS benefit with ibrutinib remained in the final analysis after 6-year of follow-up. 20 Patients with ≥2 prior therapies and those with TP53 or SF3B1 mutations had shorter PFS.…”
Section: Early Trials Of Ibrutinib Single Agent In the Setting Of Rmentioning
confidence: 97%
See 2 more Smart Citations